Pengaruh Dimensi Bauran Promosi Terhadap Keputusan Pembelian Kartu Perdana Telkomsel - M. Syarif Hidayatullah Elmas; Hermanto Hermanto; Agung Yatiningrum; Nurul Mega Rosita; Elok Mia Rianti (Ecobuss, 2018)
The purpose of this study is to determine the effect of promotional mix dimensions on the purchase decisions Telkomsel starter cards among students of the FE, UPM Probolinggo. Aspects covered in the promotion mix include advertising, personal selling, public relations, sales promotion, and direct marketing of Telkomsel's starter pack. Factors of the purchasing decisions discussed include decisions about product types, product decisions, brand decisions, sales decisions, product decisions, purchasing decisions, and decisions about how to pay. The population of this study is all students of Faculty of Economics who use Telkomsel prime card. Of these populations, taken some students as a sample of research that is 40 students. This study uses a statistical calculator tool that is SPSS 22. The most significant influential promotion mix is ​​personal selling and direct marketing. In addition, about 42.4% of independent variables (X) affect the dependent variable (Y), while 57.6% is explained by other factors outside the variable. Keywords: Advertising, Personal Sales, Public Relations, Sales Promotion, Direct Marketing, and Purchase Decision.